Persistence of Staphylococcus aureus: Multiple Metabolic Pathways Impact the Expression of Virulence Factors in Small-Colony Variants (SCVs) - Tuchscherr, Lorena; Löffler, Bettina; Proctor, Richard A. (Frontiers in Microbiology, 2020)
Staphylococcus aureus is able to survive within host cells by switching its phenotype to the small-colony variant (SCV) phenotype. The emergence of SCVs is associated with the development of persistent infections, which may be both chronic and recurrent. This slow-growing subpopulation of S. aureus forms small colonies on solid-medium agar, is induced within host cells, presents a non-homogenous genetic background, has reduced expression of virulence factors and presents a variable phenotype (stable or unstable). While virtually all SCVs isolated from clinical specimens can revert to the parental state with rapid growth, the stable SCVs recovered in clinical specimens are been found to contain specific mutations in metabolic pathways. In contrast, other non-stable SCVs are originated from regulatory mechanisms involving global regulators (e.g., sigB, sarA and agr) or other non-defined mutations. One major characteristic of SCVs was the observation that SCVs were recovered from five patients with infections that could persist for decades. In these five cases, the SCVs had defects in electron transport. This linked persistent infections with SCVs. The term “persistent infection” is a clinical term wherein bacteria remain in the host for prolonged periods of time, sometimes with recurrent infection, despite apparently active antibiotics. These terms were described in vitro where bacteria remain viable in liquid culture medium in the presence of antibiotics. These bacteria are called “persisters”. While SCVs can be persisters in liquid culture, not all persisters are SCVs. One mechanism associated with the metabolically variant SCVs is the reduced production of virulence factors. SCVs have consistently shown reduced levels of RNAIII, a product of the accessory gene regulatory (agrBDCA) locus that controls a quorum-sensing system and regulates the expression of a large number of virulence genes. Reduced Agr acitivity is associated with enhanced survival of SCVs within host cells. In this review, we examine the impact of the SCVs with altered metabolic pathways on agr, and we draw distinctions with other types of SCVs that emerge within mammalian cells with prolonged infection.